Kajian Hukum Mengenai Relevansi Putusan Mahkamah Konstitusi tentang Ambang Batas Pencalonan Presiden dan Wakil Presiden di Indonesia - Agustien Cherly Wereh (Lembaga Penelitian dan Pengabdian Universitas Negeri Manado, 2022)
The holding of the general election for President and Vice President which is held simultaneously but in the implementation of the general election still uses the threshold conditions. The threshold conditions are obtained from the results of the previous election. The Constitutional Court affirmed that the threshold requirement for simultaneous general elections is constitutional. The purpose of the study is to examine the relevance of the Presidential Threshold with simultaneous elections. The research method is normative legal research. The types of data used are primary data and secondary data. From the results of the study, it can be concluded that the Presidential Threshold must follow the development of the general election, namely simultaneous elections and the Presidential Threshold only limiting the people's right to get many presidential and vice presidential candidates.